2010
DOI: 10.1007/s10311-010-0283-1
|View full text |Cite
|
Sign up to set email alerts
|

A novel procedure for acid-catalysed K2FeO4 oxidation of benzyl alcohol in organic phase

Abstract: Recent investigations have shown that ferrate(VI) salts oxidize organic compounds in aqueous phases with fast reaction from seconds to minutes and poor selectivity. Few studies have used ferrate(VI) in organic phases. The main issues are the poor solubility of K 2 FeO 4 in common organic solvents and the low reaction rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…It was interesting to note that the admissible limit of arsenic in drinking water as suggested by WHO (10 ppb) was crossed only when pH of the solution was increased above 6.08, while 100% removal was observed at pH 3.54 (Table , column 5). At lower pH, the oxidative nature of ferrate is increased . Moreover, protonation of the surface of adsorbent at low pH also facilitates the adsorption of negatively charged arsenate (AsO 4 3– ) ions through electrostatic attraction.…”
Section: Resultsmentioning
confidence: 99%
“…It was interesting to note that the admissible limit of arsenic in drinking water as suggested by WHO (10 ppb) was crossed only when pH of the solution was increased above 6.08, while 100% removal was observed at pH 3.54 (Table , column 5). At lower pH, the oxidative nature of ferrate is increased . Moreover, protonation of the surface of adsorbent at low pH also facilitates the adsorption of negatively charged arsenate (AsO 4 3– ) ions through electrostatic attraction.…”
Section: Resultsmentioning
confidence: 99%
“…4, only 37.9% desulfurization rate was obtained without SZ. This is understandable, because of the poor solubility of K 2 FeO 4 in common organic phases and the low reaction rate [6]. The desulfurization rate increased rapidly with the SZ amount at the beginning, reaching 59.2% for 0.20 g of SZ.…”
Section: Optimization Of Oxidantion Conditionsmentioning
confidence: 99%
“…Especially, SO 4 2− /M x O y catalyst exhibits excellent catalytic activity and selectivity for all acid-catalyzed reactions and therefore has attracted much attention [5]. Previous studies by our group revealed that the reactivity of K 2 FeO 4 for oxidation of benzyl alcohol in organic solvent can be greatly enhanced by addition of a small amount of acid solution at room temperature [6,7]. Therefore, we speculated that a solid superacid would be a promising catalyst for K 2 FeO 4 -mediated ODS.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, high redox potentials up to 2.2 V can be theoretically obtained at low pH, but its rapid decomposition makes the fascinating oxidizing power inaccessible in real applications. Second, ferrate(VI) solid is insoluble in organic solvents,, thus most of its oxidizing capability is actually “hidden” inside the solid structure and the accessible surface will be gradually passivated by the resultant Fe III during reaction, which are undesirable for efficient/effective oxidative transformations. Third, the hazardous organic solvents (e.g., benzene, cyclohexane, pentane) and corrosive conc.…”
Section: Figurementioning
confidence: 99%